Chemical input reduction in the arabinoxylan and lignocellulose alkaline extraction and xylooligosaccharides production - de Figueiredo, Franciane Cristina [UNESP] (2017)
Lignocellulosic material breakdown by hydrolysis is an important step to open new perspectives for bioenergy and special foods production like prebiotic xylooligosaccharides. Improvement of lignocellulose and arabinoxylan alkaline extraction from sugarcane bagasse and enzymatic hydrolysis were performed. Treatments 1 (10% KOH at 70ï¿½ï¿½C), 3 (5% KOH at 121ï¿½ï¿½C) and ZD method (24% KOH at 35ï¿½ï¿½C) showed solid lignocellulose recovery of respectively 75.2%, 74.2% and 73%. A range of 24.8–27% extracted material with high arabinoxylan content (72.1–76.3%) was obtained with these treatments. Treatment 1 and 3 exhibited great KOH reduction in the method reaction, 54.1% and 76.2%, respectively. Likewise, in treatment 3 there was a decrease in ethanol consumption (40.9%) when compared to ZD method. The extracted arabinoxylan showed susceptibility to enzymatic hydrolysis with high solid loading (7%) since Trichoderma reesei xylanases were advantageous for xylose production (54.9%), while Aspergillus fumigatus xylanases achieved better XOS production (27.1%).